EVALUATION OF DRUG-RELATED PROBLEMS (DRPS) IN INPATIENT STROKE PATIENTS AT DR. HASAN SADIKIN CENTRAL GENERAL HOSPITAL, BANDUNG - Rachma Mahindra, Meysaroh
Stroke is the leading cause of death in Indonesia, with the incidence rate continuing to increase every year. One effort to manage stroke is through pharmacological therapy, which has the potential to cause drug-related problems (DRPs). It is very likely that stroke patients have comorbidities or are on multiple medications, increasing the potential for DRPs. This study aims to identify the potential occurrence of DRPs and analyze factors associated with their occurrence in stroke patients. The research method is retrospective observational with a cross-sectional design, using electronic medical records of inpatients diagnosed with stroke from January to August 2023 at RSUP Dr. Hasan Sadikin Bandung. The number of patients analyzed was 196. The results of the study showed that there were 356 potential DRP events, with an average of 1.8 events per patient. The types of DRPs included suboptimal treatment (34 events, 17%), untreated indications (81 events, 41%), potential adverse drug reactions (ADR) (196 events, 100%), and unnecessary treatment (45 events, 23%). There was no relationship between the risk factors of age, duration of hospitalization, and the number of drugs used and the potential for DRP events in patients. However, there is a weak relationship between the number of comorbidities and the potential for DRPs (r=0.1). The results of the bivariate analysis showed no significant difference in the potential incidence of DRPs between male and female patients, nor between patients who smoked and those who did not.